Coherent spin and quasiparticle dynamics in solution-processed layered 2D lead halide perovskites - Giovanni, David (2018)
Layered 2D halide perovskites with their alternating organic and inorganic atomic layers that form a self‐assembled quantum well system are analogues of the purely inorganic 2D transition metal dichalcogenides. Within their periodic structures lie a hotbed of photophysical phenomena such as dielectric confinement effect, optical Stark effect, strong exciton–photon coupling, etc. Detailed understanding into the strong light–matter interactions in these hybrid organic–inorganic semiconductor systems remains modest. Herein, the intricate coherent interplay of exciton, spin, and phonon dynamics in (C6H5C2H4NH3)2PbI4 thin films using transient optical spectroscopy is explicated. New insights into the hotly debated origins of transient spectral features, relaxation pathways, ultrafast spin relaxation via exchange interaction, and strong coherent exciton–phonon coupling are revealed from the detailed phenomenological modeling. Importantly, this work unravels the complex interplay of spin–quasiparticle interactions in these layered 2D halide perovskites with large spin–orbit coupling.